Climate Change and Food Production in FatehpurDistrict of Ganga-Yamuna Doab, UttarPradesh - Singh, Shashi Bala (National Geographical Journal of India, 2022)
The goals of sustainable development are to end hunger, achieve food security and improve nutritional status. Food security is dependent on agriculture in two ways: firstly, it ensures the supply of food grains and secondly, provides the livelihood for 36% (source) of the total workforce. Agriculture, in turn, is dependent on climate. Therefore, climate change, implying any alteration in parameters such as temperature and humidity, govern crop growth and therefore has a consequential impact on the quantity of food grains produced, gradually affecting the food security of a region. With this chain of understanding, an attempt has been made in this paper to analyse the impact of climate change on agricultural production in Fatehpur district of Ganga-Yamuna Doab, a region that experiences challenges for food security due to both low agricultural production and lack of nutritious food. Secondary data has been used in the context of food security of the area